Pengaruh Kepemimpinan Transformasional, Work Life Balance, Role Clarity, Dan Psychological Empowerment Terhadap Kinerja Karyawan ( Studi Kasus Pada Kantor Pegadaian Di Kabupaten Malang ) - Putra, Satrio Airlangga; Rizal, Mohammad; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study attempts to measure the contribution of Transformational Leadership, Work-Life Balance, Role Clarity, and Psychological Empowerment on Employee Performance. Data were collected using a saturation technique from 33 respondents through a questionnaire and a Likert Scale. Data analysis was performed using multiple linear regression and hypothesis testing (F and t tests). The results showed that simultaneously and partially, all four variables had a positive and significant influence on employee performance. Keywords : Transformational Leadership, Work-Life Balance, Role Clarity, and Psychological Empowerment on Employee Performance